2020
DOI: 10.3390/ijerph17072353
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Airborne Mercury: Comparison of Different Techniques in the Monte Amiata District, Southern Tuscany, Italy

Abstract: In the present study, mercury (Hg) concentrations were investigated in lichens (Flavoparmelia caperata (L.) Hale, Parmelia saxatilis (L.) Ach., and Xanthoria parietina (L.) Th.Fr.) collected in the surrounding of the dismissed Abbadia San Salvatore Hg mine (Monte Amiata district, Italy). Results were integrated with Hg concentrations in tree barks and literature data of gaseous Hg levels determined by passive air samplers (PASs) in the same area. The ultimate goal was to compare results obtained by the three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Lichens are known to accumulate both elemental (Hg 0 ) and ionic (Hg 2+ ) mercury, i.e., the two main forms of atmospheric Hg [ 13 ], up to very high concentrations, even 4–5 orders of magnitude higher than those found in samples grown in remote areas [ 14 , 15 ], without showing signs of physiological stress, despite the known phytotoxicity of this element [ 16 ]. Mercury is accumulated mainly in the elemental and ionic forms [ 14 , 15 ], but in some peculiar cases, such as highly contaminated mining areas, the exposition of particulate Hg may also relevantly contribute to the total Hg content of lichen samples [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lichens are known to accumulate both elemental (Hg 0 ) and ionic (Hg 2+ ) mercury, i.e., the two main forms of atmospheric Hg [ 13 ], up to very high concentrations, even 4–5 orders of magnitude higher than those found in samples grown in remote areas [ 14 , 15 ], without showing signs of physiological stress, despite the known phytotoxicity of this element [ 16 ]. Mercury is accumulated mainly in the elemental and ionic forms [ 14 , 15 ], but in some peculiar cases, such as highly contaminated mining areas, the exposition of particulate Hg may also relevantly contribute to the total Hg content of lichen samples [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study [ 41 ] found Hg concentrations decreasing from 2510 to 70 ng g −1 at increasing distances from a chlor-alkali plant located near Grenoble, with a contamination radius of about 2 km, while [ 40 ] measured a background value of Hg (148 ng g −1 ) in epiphytic lichens collected at a distance of 8 km from a chlor-alkali plant in Canada and the highest Hg concentration (3660 ng g −1 ) at 250 m distance. A concentration decreases within a radius of 3 km in lichens collected at increasing distances from abandoned mining and smelting plants (Abbadia San Salvadore, Italy) was observed by [ 37 ] and [ 67 ]. A comparative study of Hg concentrations in air and in epiphytic lichens in a former Hg mining area in Idrija, Slovenia, was performed by [ 39 ], who found a good correlation between Hg concentrations in air and lichens.…”
Section: Discussionmentioning
confidence: 97%
“…This accumulation is probably due to the various quarries surrounding the study station, which is located between two mountains, i.e., Djebel Sakreen to the south and Djebel Youssef to the north. Overall, the region has 12 quarries, which might negatively affect the environment (Issah et al 2010;Midhat et al 2019;Rimondi et al 2020). The high rates of MTE accumulation at Bir Hadada is presumably not only linked to a large number of quarries, but also related emissions from intensive agricultural operations which degrade the environment through the release of pesticides and chemicals that generate associated toxic heavy metal particles suspended in the environment (Wei and Yang.…”
Section: Discussionmentioning
confidence: 99%